Bioinspired Colloidal Photonic Composites: Fabrications and Emerging Applications. Issue 52 (24th April 2022) - Li, Miaomiao; Lyu, Quanqian; Peng, Bolun; Chen, Xiaodong; Zhang, Lianbin; Zhu, Jintao
Abstract: Organisms in nature have evolved unique structural colors and stimuli‐responsive functions for camouflage, warning, and communication over millions of years, which are essential to their survival in harsh conditions. Inspired by these characteristics, colloidal photonic composites (CPCs) composed of colloidal photonic crystals embedded in the polymeric matrix are artificially prepared and show great promise in applications. This review focuses on the summary of building blocks, i.e., colloidal particles and polymeric matrices, and constructive strategies from the perspective of designing CPCs with robust performance and specific functionality. Furthermore, their state‐of‐the‐art applications are also discussed, including colorful coatings, anti‐counterfeiting, and regulation of photoluminescence, especially in the field of visualized sensing. Finally, current challenges and potential for future developments in this field are discussed. The purpose of this review is not only to clarify the design principle for artificial CPCs but also to serve as a roadmap for the exploration of next‐generation photonic materials. Abstract : Colloidal photonic composites bioinspired by organic organisms combine ordered photonic structures and functional polymeric matrices, which show both structural color of photonic crystals and functionality and responsiveness of the polymeric matrix. Colloidal photonic composites exhibit a variety of promising applications, from colorful coatings to visual sensors, anti‐counterfeiting, and regulation of photoluminescence.